Water quality changes using GIS-based approach at seagrass meadows along the straits of Johor - Syarifuddin, Misbari; Mazlan, Hashim (AIP Publishing, 2023)
Industrialization and urbanization promote socio-economy development but they unwittingly cause environmental problems. Land use change always brings about the changes of ecological components including water quality and richness of marine communities. Rapid alteration in coastal landscape, increasing density of residential area and intensive reclamation since 2013 in Merambong coast area causes subtle changes of water quality compared to 2009 where coastal development is relatively moderate. Interaction between water quality changes and seagrass biomass changes in tropical water remains intriguing and indistinct. Thus, this study focuses to analyze water quality changes that cause intensive pollution and changes in water quality that lead to the gradual changes in seagrass biomass within a 4-year interval along the Straits of Johor. Water quality checker of the Horiba U-52 model is used during field sampling to measure seven main water quality parameters from 35 sampling points. Using Landsat 8 OLI image, each water quality parameter is visualized and interpolated using the GIS system on known points of water sampling and the accuracy is assessed. The study found that the changes of water quality of tropical water is directly proportional with the changes of seagrass biomass, primarily due to increasing turbidity from the consecutive flows of pollutant as the consequence of coastal alteration for urbanization and industrial expansion. The increment of >30% in total dissolved solids content, turbidity and dissolved oxygen is the most obvious changes in the reclamation area. Heavy load of sediment in parallel with coastal development is the most potential threat to water quality maintenance. Findings from the study are very important to support SDG 14 and as a reference for the governance of stakeholders and policy makers in providing excellent services to the coastal community, sustainable coastal planning and estimation of natural resource productivity in local scale.